HIGH PRESSURE CAUSTIC LEACH METHODS AND PROCESSES FOR RECOVERY OF SCANDIUM AND RARE-EARTH OXIDES - GRAF, CHRISTIAN; OYEDIRAN, YEMI; RISCHE, DANIEL (2023)
Despite the abundance of scandium, its commercial applications continue to be limited by the absence of reliable, secure, stable and long-term production. The subject-matter disclosed herein provides for a method for extracting Rare Earth Elements (REE), scandium and /or Rare-Earth Oxides (REO) from ore and mineral concentrates, the method comprising: providing Rare Earth Elements (REE) and/or scandium bearing feedstock; a high-pressure caustic (HPC) leaching step, comprising leaching the feedstock in an alkali solution at a first temperature for a target period of time and at a given pressure to produce a leachate slurry; extracting a solid residue from the leachate #slurry; leaching of the solid residue in a mineral acid to form a primary leach solution; extracting scandium and/or REE from the primary leach solution; and/or precipitating REE remaining in the raffinate to form a mixed REE-carbonate to thereby facilitate the extraction of REO.